MACROBENTHOS DIVERSITY ON KELAPA DUA ISLAND, SERIBU ISLAND NATIONAL PARK, DKI JAKARTA - Katarina Hesty Rombe; Agus Surachmat; Etti Sartika Rahayu (Berkala Perikanan Terubuk, 2022)
Macrobenthos are aquatic organisms that live on the bottom of the waters with relatively slow movements which are strongly influenced by the basic substrate and water quality. This data collection aims to identify macrobenthos, calculate the abundance, diversity and dominance as well as the composition of macrobenthic species and to determine the quality of the waters on Kelapa Dua Island. The method used in this activity uses a transect line technique that is pulled along 50 meters in a perpendicular direction from the coast to the sea, on each transect a frame measuring 1x1 meter is placed. Observations were made at 3 stations, where each station was repeated 3 times. Observations showed that there were two classes of macrobenthos, namely gastropods and bivalves. From the results of data collection obtained two classes of macrobenthos, namely gastropods and bivalves. The abundance value (Di) is 1685 Ind/m², the diversity value (H') is 23.56, and the dominance value (C) is 0.51, and the species composition value (9.09%). Water quality measurements obtained from the data collection include, water temperature (C°) in the range of 29-33, depth (cm) 20-42, current velocity (m/s) 0.06-0.08, salinity (ppt ) 20-27 and pH 6, and the water substrate contained coarse sand, fine sand, rubble.